Bank Solvency and Funding Cost - Aymanns, Christoph; Caceres, Carlos; Daniel, Christina; Schumacher, Liliana (Washington, D.C. : International Monetary Fund, 2016)
Understanding the interaction between bank solvency and funding cost is a crucial pre-requisite for stress-testing. In this paper we study the sensitivity of bank funding cost to solvency measures while controlling for various other measures of bank fundamentals. The analysis includes two measures of bank funding cost: (a) average funding cost and (b) interbank funding cost as a proxy of wholesale funding cost. The main findings are: (1) Solvency is negatively and significantly related to measures of funding cost, but the effect is small in magnitude. (2) On average, the relationship is stronger for interbank funding cost than for average funding cost. (3) During periods of stress interbank funding cost is more sensitive to solvency than in normal times. Finally, (4) the relationship between funding cost and solvency appears to be non-linear, with higher sensitivity of funding cost at lower levels of solvency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet